STUDY OF MARINE ECOTOURISM POTENTIAL THE SIRANDAH ISLAND BUNGUS TELUK KABUNG REGENCY OF WEST SUMATRA PROVINCE - Gustasya, Yosy; Yoswaty, Dessy; Elizal, Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Sirandah Island is one of the small islands in Padang City, a tourist destination of the bustling islands visited today. This studywas conducted inMay 2018, aims to analyze the suitability of the area owned by Sirandah Island by taking into account the land suitability index of Sirandah Island, so that it can be developed as a tourist area and marine ecotourism.The method used is tourism conformity analysis with calculation of score and weight. The results show that the condition of the coastal area around Sirandah Island is still in good condition. Overall the island is surrounded by shore beaches, white sandy sediments, classified as sloping, the coast is wide and wide. Waters around the island has a depth of the sea reaches 50 m (near the coast is still 0 - 10 m), belonging to shallow water. The surface current condition is quite low, ranging from 0.07 - 0.12 m / s. The quality of seawater around the island is also quite good, the temperature value (SPL) ranges from 31 ° C, pH 6, salinity 34 - 35 ppt and 10 m (10%) water transparency. The condition of coastal and aquatic characteristics of Sirandah Island is very supportive for island tourism, namely beach tourism (recreation) very appropriate (S1) with value 86,96%, coastal tourism category boating, banana boat, and jet ski according to (S2) with value 17.33. Keyword : level of conformity, marine ecotourism, Sirandah Island